4-BOYUTLU ÖKLİD UZAYINDA BİSHOP ÇATIYA GÖRE BAZI İLİŞKİLİ EĞRİLER - DUYAN, AHMET (Fırat Üniveristesi, 2020)
Öklid uzayında eğriler teorisinde farklı çatılara göre birçok çalışma yapılmıştır. Birçok bilim adamı bu teoride Frenet çatı, Bishop çatı, Adapted çatı gibi çatıları çalışmıştır. Bu çatılar eğriler ile ilgili karakterizasyonlarda bize yardımcı olur. Bu çalışmada, 4-boyutlu Öklid uzayında bishop çatıya göre Frenet eğrisi ile ilişkili eğriler incelenmiştir. Bu çatıya göre Frenet eğrilerin doğrultman eğrileri ve rektifyan eğrileri verilmiştir.

Many studies have been done according to different frames of the theory of curves in Euclidean Space. Many scientists have studied frames such as Frenet frame, Bishop frame, Adapted frame in this theory. These frames help us in the characterization of curves. In this study, associated curves with Frenet curve according to Bishop frame in 4-dimensional Euclidean space are investigated. Direction and rectifying curves of the frenet curve according to this frame are given.
Associated curves according to bishop frame in 4-dimensional euclidean space
Keywords: Matematik